2018
DOI: 10.1002/ana.25207
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation stimulates neural repair in Friedreich's ataxia mice

Abstract: ObjectiveFriedreich's ataxia is an incurable inherited neurological disease caused by frataxin deficiency. Here, we report the neuroreparative effects of myeloablative allogeneic bone marrow transplantation in a humanized murine model of the disease.MethodsMice received a transplant of fluorescently tagged sex‐mismatched bone marrow cells expressing wild‐type frataxin and were assessed at monthly intervals using a range of behavioral motor performance tests. At 6 months post‐transplant, mice were euthanized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Intrathecal delivery of bone marrow-derived mesenchymal stem cells, both autologous and allogeneic, to the YG8R FRDA mouse model has been reported to increase frataxin expression in the DRG, to increase the levels of antioxidant enzymes, and to improve motor function [127]. Similar findings have been reported by Kemp and colleagues [130], and these investigators have also shown that stem cell-derived factors [128], as well as the cytokines granulocyte-colony stimulating factor (G-CSF) and stem cell factor (SCF) [131] have similar effects of ameliorating the disease phenotype in the YG8R FRDA mouse model, and each of these treatments induced frataxin expression in affected tissues. As to how stem cells increase frataxin levels, Rocca and colleagues recently reported the transfer of wild-type frataxin and Cox8 mitochondrial proteins from HSPC-derived microglia/macrophages to neurons and muscle myocytes in the YG8R mouse model [129].…”
Section: Approach 3: Increasing Frataxin Proteinsupporting
confidence: 78%
“…Intrathecal delivery of bone marrow-derived mesenchymal stem cells, both autologous and allogeneic, to the YG8R FRDA mouse model has been reported to increase frataxin expression in the DRG, to increase the levels of antioxidant enzymes, and to improve motor function [127]. Similar findings have been reported by Kemp and colleagues [130], and these investigators have also shown that stem cell-derived factors [128], as well as the cytokines granulocyte-colony stimulating factor (G-CSF) and stem cell factor (SCF) [131] have similar effects of ameliorating the disease phenotype in the YG8R FRDA mouse model, and each of these treatments induced frataxin expression in affected tissues. As to how stem cells increase frataxin levels, Rocca and colleagues recently reported the transfer of wild-type frataxin and Cox8 mitochondrial proteins from HSPC-derived microglia/macrophages to neurons and muscle myocytes in the YG8R mouse model [129].…”
Section: Approach 3: Increasing Frataxin Proteinsupporting
confidence: 78%
“…Abundant HSPCs engrafted into affected tissues and differentiated into microglia in brain and spinal cord, and macrophages in DRG, heart and muscle, and led to frataxin transfer to the diseased neurons and myocytes. Another study ( Kemp et al, 2018 ) subsequently reported similar results where transplantation of wild type bone marrow (BM) cells to YG8R FRDA mice improved motor coordination, rescued neurobehavioral deficits and resulted in engraftment of bone marrow-derived macrophages/microglia in DRG, spinal cord and cerebellum. Altogether, these data represent the proof of concept that the different complications associated with FRDA could be treated by a HSPC transplantation.…”
Section: Introductionmentioning
confidence: 78%
“…Release of haematopoietic stem and progenitor cells into the peripheral circulation may have important therapeutic implications in FA. Our studies investigating bone marrow transplantation strategies in humanised FA mouse models have revealed that G-CSF can stimulate the recruitment of bone marrow cells to areas of FA-associated pathology to promote nerve cell repair 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Continued research and technological advances in regenerative medicine have increased interest in developing neuro-reparative stem cell-based therapies for people with FA. Using a humanised murine model of FA we demonstrated that treatment with the stem cell mobilising cytokines granulocyte-colony stimulating factor (G-CSF) and stem cell factor had pronounced effects on frataxin levels within the nervous system and improved clinical, biochemical and pathological parameters associated with the disease 10 , 11 . Moreover, we have also shown that these agents had neuroprotective effects in FA, increased stem cell mobilisation to sites of pathology and stimulate neural repair 10 .…”
Section: Introductionmentioning
confidence: 99%